Manejo de pesticidas y salud laboral de los trabajadores agrícolas afiliados al seguro social campesino en la comunidad de Guntualó. - Quisanga Moreno, José Ramón (2015)
The use of pesticides has produced great agricultural benefits and, at the same time, serious health problems. Pesticides not only affect the agricultural worker, who suffers the most exposure, but also the environment and therefore to the community that is affected by pollution of food, water, soil and air. Developing long-term effects such as non-Hodgkin lymphoma, which can trigger hypothyroidism thyroid cancer but takes appropriate treatment. In the community of affiliated farmers Guantualó the rural social security, job after spraying have the following health problems: extreme fatigue, headache, sore throat, chemical conjunctivitis, dizziness and chemical dermatitis. The Problem. Inadequate exposure to pesticides and other agrochemicals constitutes a major occupational hazards. These cause poisoning and death, and in some cases, occupational cancer and reproductive disorders.